Association between the person-centered maternity care experience and mental health after delivery in urban and rural Dhading, Nepal: a cross-sectional study - Yuri Tomita; Junko Kiriya; Ram Chandra Silwal; Ken Ing Cherng Ong; Akira Shibanuma; Masamine Jimba (BMC, 2023)
Abstract Background Person-centered maternity care is a component of quality care, which includes effective communication, respect, and dignity. Supportive care has a positive effect on mothers' perinatal experience. In contrast, negative childbirth experiences can cause psychological problems. However, the impact of person-centered maternity care experience on mothers' mental health after delivery remains unknown. Therefore, in this study, we examined the association between person-centered maternity care experience at healthcare facilities and maternal mental health after delivery among Nepali women. Methods We conducted a cross-sectional study in urban and rural areas in Dhading District, Nepal. Participants were women who gave birth at public healthcare facilities, and their baby's age was between 1 and 12 months. After purposively selecting the target areas, we recruited the women from July to August 2019 and interviewed them using questionnaires. We conducted multiple regression analyses to analyze the association between delivery care experience and depressive symptoms and the association between delivery care experience and mental well-being. Results In total, 595 women were included in the data analysis. The experience of better person-centered maternity care was associated with lower depressive symptom scores in urban (unstandardized coefficient [B]= − 0.09, p < 0.001) and rural areas (B= − 0.10, p < 0.001). Moreover, the experience of better person-centered maternity care was associated with higher mental well-being scores in both urban (B= 0.30, p < 0.001) and rural areas (B= 0.15, p = 0.017). Conclusions Person-centered maternity care was associated with lower depressive symptom scores and higher mental well-being, regardless of the setting in Nepal. Person-centered maternity care during childbirth can potentially improve mental health after delivery. Maternity care should be improved with more attention to person-centered maternity care aspects.